CRM technology and KAM performance: The mediating effect of key account-related knowledge - Hanna Salojärvi; Liisa-Maija Sainio (jbm - Journal of Business Market Management, 2015)
This paper examines the effect of customer relationship management (CRM) technology investment and key account-related knowledge on suppliers' key account management (KAM) performance. The findings are based on survey data gathered from large Finnish industrial suppliers and subjected to factor analysis and hierarchical linear regression. The results show that CRM technology is positively related to key account-related knowledge. In addition, the results show that the effect of CRM technology investment on KAM performance is fully mediated by key accountrelated knowledge. The study contributes to previous literature on the consequences of CRM technology investments in shedding light on the importance of the nature of the knowledge acquired. The implementation of CRM technology is not enough as it is the key account-related knowledge that has a stronger effect on the ability of the supplier to manage its strategically most important customers.
urn:nbn:de:0114-jbm-v8i1.1050
Keywords: 650; Customer knowledge; CRM; Customer Relationship; Key Account Management